Pengembangan, Uji Validitas, Dan Uji Reliabilitas Instrumen Tes Diagnostik Berformat Five Tier Pada Materi Hukum Newton - Audina Paramitha Azahra; Wasis Wasis (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
Students' understanding of physics concepts differs from one student to another. Based on the results of the five-tier conceptual diagnostic test, students' conceptions can be grouped based on several levels of conception. One of them is a misconception. This study aims to develop a five-tier format test instrument on Newton's Law material, test the validity and reliability of the test instrument, and use test instruments that have been developed to determine the level of conception of 20 students. The question instrument developed has been declared valid and reliable. The results of the final trial of 20 students showed that more than 50% of students experienced misconceptions.